Acordos bilaterais de comércio entre as economias do Brics: Uma abordagem de equilíbrio geral - Lucas P. do C. Ferraz (Instituto de Pesquisa Econômica Aplicada (IPEA), 2013)
– This paper contrasts alternative preferential trade arrangements involving Brazil and each of the remaining Brics economies: China, India, Russia and South Africa. Bilateral trade liberalization scenarios are simulated under a perfect competition market structure, using the GTAP general equilibrium framework. Traditional allocative effects are described for the Brazilian economy, as a way to foresee the most relevant first round domestic effects at the macro and micro level. Winners and losers are traced out for 56 sectors in the Brazilian economy, under each alternative simulation scenario. The emergence of China as a significant trade pattern is confirmed in the simulation results. Competitive effects are also significant in the case of a preferential trade agreement involving Brazil and India as well as Brazil and Russia, despite current low levels of bilateral trade. More modest first round effects are obtained in the case of a PTA involving Brazil and South Africa.
Keywords: F11; F14; D61; 330; bilateral agreements; terms of trade; computable general equilibrium; comparative advantage